Molecular genetics of Drosophila -actinin: mutant alleles disrupt Z disc integrity and muscle insertions. - Fyrberg, E.A.; Kelly, M.; Ball, E.; Fyrberg, C.C.; Reedy, M.C. (Journal of Cell Biology, 1990)
We have isolated a Drosophila melanogaster alpha-actinin gene and partially characterized several mutant alleles. The Drosophila protein sequence is very similar (68% identity) to those of chicken alpha-actinin isoforms, but less closely related (30% identity) to Dictyostelium alpha-actinin. The gene is within subdivision 2C of the X chromosome, coincident with 15 lethal (1)2Cb mutations. At least four alleles, l(1)2Cb1, l(1)2Cb2, l(1)2Cb4, and l(1)2Cb5 are interrupted by rearrangement breakpoints and must be null. In all four cases, hemizygous mutants complete embryogenesis and do not die until the second day of larval growth, signifying that either the role of alpha-actinin in nonmuscle cells is redundant or that a distinct and only distantly related gene encodes the non-muscle isoform. Allelic but less severely affected fliA mutants are apparently due to point mutations, and develop into adults having thoracic muscle abnormalities. EM of mutant muscles reveals that Z discs and myofibrillar attachments are disrupted, whereas epithelial "tendon" cells are less affected. We discuss these phenotypes in the light of presumed in vivo alpha-actinin functions.